Nonwoven fabric and its manufacturing method, as well as liquid-impregnated sheet and wiping sheet

By using cellulose fibers, adhesive layer-type composite fibers and non-adhesive layer-type composite fibers in non-gauzes, forming a pseudo-network structure, the existing non-gauzes have poor morphological stability and unsatisfactory liquid release rate have been solved, and high morphological stability and good liquid treatment performance have been achieved.

JP7663556B2Active Publication Date: 2025-04-16KURARAY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022509517
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-24
Filing Date
2021-03-09
Publication Date
2025-04-16
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

The existing non-gauze has poor morphological stability when used, and the liquid retention and release rate are not ideal, and it is easy to slip when folded, making it inconvenient to handle.

Method used

A non-gauze structure including cellulose fibers, adhesive layer-type composite fibers and non-adhesive layer-type composite fibers are adopted, wherein the adhesive layer-type composite fibers form an adhesive portion at the intersection to form a pseudo-network structure to improve the morphological stability of the overall non-gauze, and the liquid release rate and retention rate are controlled by adjusting the fiber ratio and treatment method.

Benefits of technology

It achieves high morphological stability of non-gauze, good liquid retention and release performance, is not easy to slip when folded, is easy to handle when used, and reduces friction and burden on the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663556000002
    Figure 0007663556000002
  • Figure 0007663556000003
    Figure 0007663556000003
  • Figure 0007663556000004
    Figure 0007663556000004
Patent Text Reader

Abstract

The present invention provides: a nonwoven fabric; a method for producing this nonwoven fabric; a sheet impregnated with a liquid; and a wiping sheet. This nonwoven fabric (10) contains cellulose fibers (13), bonded sheath-core type composite fibers (11) and non-bonded sheath-core type composite fibers (14); the content of the bonded sheath-core type composite fibers relative to the total mass of the nonwoven fabric is from 5% by mass to 20% by mass; the content of the cellulose fibers relative to the total mass of the nonwoven fabric is not less than 45% by mass but less than 90% by mass; the bonded sheath-core type composite fibers have bonded parts at intersection points at which fibers intersect with each other and are bonded with each other; and the non-bonded sheath-core type composite fibers contain an ethylene-vinyl alcohol copolymer in sheath parts.
Need to check novelty before this filing date? Find Prior Art

Description

Related Applications

[0001] This application claims priority from Japanese Patent Application No. 2020-53332, filed on March 24, 2020, the entire disclosure of which is incorporated herein by reference. [Technical Field]

[0002] The present invention relates to nonwoven fabrics, liquid-impregnated sheets, and wiping sheets. [Background technology]

[0003] In recent years, liquid-containing sheets, which are nonwoven fabrics impregnated with liquid, have come into use due to their ease of use. These liquid-impregnated sheets are used as face masks, spreader sheets, wipes, etc.

[0004] Patent Document 1 (JP 2008-261067 A) discloses a nonwoven fabric sheet formed by entangling solvent-spun cellulose fibers having a fiber length of 30 to 60 mm with sheath-core composite fibers, the sheath-core composite fibers comprising a sheath and a core, the sheath being an ethylene-vinyl alcohol copolymer and the core being a hydrophobic resin with a diameter of 5 μm to 15 μm. This document discloses that a soft and bulky entangled fiber body can be provided by forming a nonwoven fabric from a uniformly mixed state of the solvent-spun cellulose fibers and the sheath-core composite fibers using a hydroentanglement method.

[0005] Patent Document 2 (WO 2015 / 046301) discloses a liquid-retaining sheet formed of a nonwoven fabric containing 50% by mass or more of highly elastic fibers with a Young's modulus of 30 cN / T or more. This document makes it possible to provide a liquid-retaining sheet and face mask that, when impregnated with a liquid component such as a beauty serum (cosmetic), quickly returns the liquid component to the sheet even when pressed with a finger. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Laid-Open No. 2008-261067 [Patent Document 2] International Publication No. 2015 / 046301 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in Patent Documents 1 and 2, the shape stability of the nonwoven fabric when used is poor, and there is room for improvement.

[0008] SUMMARY OF THE INVENTION It is therefore an object of the present invention to provide a nonwoven fabric having excellent shape stability, and a liquid-impregnated sheet and a wiping sheet using the same.

[0009] Another object of the present invention is to provide a nonwoven fabric having excellent shape stability and good water retention and liquid release rates, and a liquid-impregnated sheet and a wiping sheet using the same.

[0010] Yet another object of the present invention is to provide a nonwoven fabric that is easy to handle because the nonwoven fabric layers do not slip when folded for use, yet has low friction between the nonwoven fabric and the skin, thereby reducing the burden on the skin, and to provide a liquid-impregnated sheet and a wiping sheet using the nonwoven fabric. [Means for solving the problem]

[0011] As a result of extensive research to achieve the above object, the inventors of the present invention have found that, from the viewpoint of improving dimensional stability, by using adhesive sheath-core composite fibers in a predetermined ratio and forming adhesive sections at the intersections where adhesive sheath-core composite fibers come into contact with each other, a pseudo-net state can be formed, thereby improving the dimensional stability of the entire nonwoven fabric.

[0012] On the other hand, the inventors discovered a new problem: the improvement in shape stability achieved by adhesive sheath-core composite fibers may not provide sufficient liquid release when the nonwoven fabric is compressed to the extent required for application to the skin, and further, the reduction in the space for retaining liquid in the nonwoven fabric may result in a decrease in water retention, requiring improvements in other fibers.As a result of extensive research into this new problem, the inventors discovered that, when a pseudo-net state is formed, the liquid release rate and water retention rate can be controlled by incorporating a cellulosic fiber and, as a third component, a non-adhesive sheath-core composite fiber having an ethylene-vinyl alcohol copolymer (EVOH) in the sheath portion into the nonwoven fabric, and by setting the proportion of the cellulosic fiber within a specific range, thereby completing the present invention.

[0013] That is, the present invention can be configured in the following manner. [Aspect 1] A nonwoven fabric containing cellulosic fibers, adhesive core-sheath type composite fibers, and non-adhesive core-sheath type composite fibers, Relative to the total mass of the nonwoven fabric, the content of the adhesive core-sheath composite fiber is 5% by mass or more and 20% by mass or less (preferably 7% by mass or more and 17% by mass or less, more preferably 8% by mass or more and 15% by mass or less), The content of the cellulosic fibers is 45% by mass or more and less than 90% by mass (preferably 50% by mass or more and less than 90% by mass, more preferably 55% by mass or more and 88% by mass or less, particularly 65% ​​by mass or more and 85% by mass or less), and The adhesive core-sheath type composite fiber has adhesive parts bonded at intersections where the fibers intersect with each other, The non-adhesive core-sheath type composite fiber is a nonwoven fabric, wherein the sheath portion contains an ethylene-vinyl alcohol copolymer. [Aspect 2] The nonwoven fabric according to aspect 1, wherein the mass ratio of the cellulosic fiber content (T) to the non-adhesive core-sheath composite fiber content (N) is T / N=99 / 1 to 51 / 49 (preferably 95 / 5 to 55 / 45, more preferably 95 / 5 to 65 / 35, and even more preferably 95 / 5 to 75 / 25). Aspect 3 The nonwoven fabric according to aspect 1 or 2, wherein the nonwoven fabric has an elongation of 40% or less (preferably 35% or less, more preferably 31% or less) when saturated with water. Aspect 4 The nonwoven fabric according to any one of aspects 1 to 3, wherein when the nonwoven fabric is impregnated with a mixed solution of distilled water and glycerin (distilled water / glycerin mass ratio = 5 / 4) in an amount of 500 mass% based on the mass of the nonwoven fabric and left for 24 hours, the nonwoven fabric has a compression hardness of 0.750 to 1.500 N / mm (preferably 0.800 to 1.400 N / mm, and more preferably 0.850 to 1.300 N / mm) at 30% compressive deformation. Aspect 5 A nonwoven fabric according to any one of aspects 1 to 4, wherein when the nonwoven fabric is impregnated with a mixed solution of distilled water and glycerin (distilled water / glycerin mass ratio = 5 / 4) in an amount of 500 mass% relative to the mass of the nonwoven fabric and left for 24 hours, the liquid release rate over 10 seconds when the nonwoven fabric is compressed and deformed by 30% is 7 to 14% (preferably 8 to 12%). Aspect 6 The nonwoven fabric according to any one of aspects 1 to 5, having a water retention rate of 1145% or more (preferably 1180% or more, and more preferably 1200% or more). Aspect 7 The nonwoven fabric according to any one of aspects 1 to 6, wherein the difference (AC) between the static friction coefficient (A) between the nonwoven fabrics themselves when they contain 400% by mass of distilled water and the static friction coefficient (C) between the nonwoven fabric and Bioskin (artificial skin) when they contain 400% by mass of distilled water is 0.0170 to 0.1000 (preferably 0.0200 to 0.0900, and more preferably 0.0300 to 0.0800). Aspect 8 Aspect 9: The nonwoven fabric according to any one of Aspects 1 to 7, wherein the coefficient of static friction (A) between the nonwoven fabrics in a state containing 400% by mass of distilled water is 0.0550 to 0.0900 (preferably 0.0600 to 0.0900, and more preferably 0.0650 to 0.0880). A nonwoven fabric according to any one of aspects 1 to 8, wherein the static friction coefficient (C) between the nonwoven fabric containing 400% by mass of distilled water and Bioskin (artificial skin) is 0.0450 or less (preferably 0.0430 or less). Aspect 10 A nonwoven fabric according to any one of aspects 1 to 9, wherein the fluff length per thickness (1) of the nonwoven fabric is 10 times or less (preferably 8 times or less, more preferably 5 times or less). Aspect 11 A liquid-impregnated sheet comprising the nonwoven fabric according to any one of the first to tenth embodiments. Aspect 12 A wiping sheet comprising the nonwoven fabric according to any one of aspects 1 to 10. Aspect 13 A method for producing the nonwoven fabric according to any one of aspects 1 to 10, comprising: a step of forming a web having an entangled structure by performing an entanglement treatment on a web containing cellulosic fibers, adhesive sheath-core composite fibers, and non-adhesive sheath-core composite fibers, the content of the adhesive sheath-core composite fibers being 5% by mass or more and 20% by mass or less and the content of the cellulosic fibers being 45% by mass or more and less than 90% by mass, based on the total mass of the web; and forming a bonded portion between the adhesive core-sheath type composite fibers in the web having the entangled structure, while not forming a bonded portion between the non-adhesive core-sheath type composite fibers. Aspect 14 A method for producing the nonwoven fabric according to aspect 13, wherein the entanglement treatment is hydroentanglement. Aspect 15 A method for producing the nonwoven fabric according to aspect 13 or 14, wherein, in the step of forming the adhesive portions, the heat treatment is performed at a temperature that is lower than the melting point of the sheath portion of the non-adhesive sheath core conjugate fiber and higher than the melting point of the sheath portion of the adhesive sheath core conjugate fiber.

[0014] It should be noted that any combination of at least two elements disclosed in the claims and / or the specification and / or the drawings is included in the present invention, and in particular any combination of two or more of the claims set forth in the claims is included in the present invention. [Effects of the Invention]

[0015] The present invention can provide a nonwoven fabric that is excellent in shape stability, water retention, liquid release, etc., and particularly preferably, can provide a nonwoven fabric that is easy to handle because the nonwoven fabric does not slip against itself when folded for use, while also reducing friction between the nonwoven fabric and the skin and reducing stress on the skin. [Brief explanation of the drawings]

[0016] The present invention will be more clearly understood from the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are for illustration and explanation purposes only and should not be used to define the scope of the present invention, which is defined by the appended claims. [Figure 1] 1 is a schematic perspective view of a nonwoven fabric according to an embodiment of the present invention. [Figure 2] FIG. 2 is a schematic enlarged plan view conceptually showing a portion of the nonwoven fabric. [Figure 3A] 3 is a partially enlarged schematic view showing a portion III in FIG. 2. FIG. [Figure 3B] 3B is a partial schematic enlarged view for explaining the adhesive portion in FIG. 3A in an enlarged manner. FIG. [Figure 4] FIG. 10 is a schematic side view illustrating how liquid released from a sample is absorbed by absorbent cotton in a liquid release rate test. [Figure 5] FIG. 2 is a schematic plan view showing a sample cut out from a nonwoven fabric used in measuring the static friction coefficient between liquid-impregnated nonwoven fabrics. [Figure 6] FIG. 2 is a schematic plan view showing a friction target member cut out from a nonwoven fabric, used when measuring the static friction coefficient between liquid-impregnated nonwoven fabrics. [Figure 7]FIG. 2 is a schematic plan view illustrating the state of a sample used when measuring the static friction coefficient between liquid-impregnated nonwoven fabrics. [Figure 8] FIG. 1 is a schematic side view illustrating a test device used to measure the static friction coefficient between liquid-impregnated nonwoven fabrics. [Figure 9] FIG. 1 is a schematic plan view showing a sample cut out from a nonwoven fabric used in measuring the static friction coefficient between a liquid-impregnated nonwoven fabric and a Bioskin plate. [Figure 10] FIG. 2 is a schematic plan view showing a sample cut out from a nonwoven fabric, used when measuring the length of fluff generated from the nonwoven fabric due to friction. [Figure 11] FIG. 2 is a schematic plan view illustrating the state of a sample used when measuring the elongation of a nonwoven fabric. DETAILED DESCRIPTION OF THE INVENTION

[0017] The nonwoven fabric of the present invention comprises cellulosic fibers, adhesive sheath-core conjugate fibers having adhesive portions, and non-adhesive sheath-core conjugate fibers having sheath portions containing an ethylene-vinyl alcohol copolymer.

[0018] (cellulosic fiber) Examples of cellulose-based fibers include vegetable fibers such as cotton, hemp, and pulp, regenerated fibers such as rayon and cupra, and refined cellulose fibers such as lyocell (Tencel). These cellulose-based fibers may be used alone or in combination. Among these, rayon is preferred because of its ease of availability and ease of handling. Furthermore, cellulose-based fibers may be partially fibrillated, but it is desirable that they are substantially unfibrillated in order to prevent fine fibers from adhering to the face.

[0019] The content of cellulose-based fibers relative to the total mass of the nonwoven fabric of the present invention is 45% by mass or more but less than 90% by mass. If the content of cellulose-based fibers is less than 45% by mass, the water retention will be low. On the other hand, if the content of cellulose-based fibers relative to the total mass of the nonwoven fabric of the present invention is 90% by mass or more, the sheet will have high density and poor liquid release properties. Preferably, the content of cellulose-based fibers relative to the total mass of the nonwoven fabric may be 50% by mass or more but less than 90% by mass, more preferably 55% by mass or more but less than 88% by mass, and particularly 65% ​​by mass or more but less than 85% by mass.

[0020] The fineness of the cellulose fibers is not particularly limited, but may be, for example, 1.2 to 2.2 dtex, more preferably 1.5 to 1.9 dtex. The average fiber length of the cellulose fibers is not particularly limited, but from the viewpoints of production workability and the mechanical properties of the nonwoven fabric, may be, for example, 10 to 100 mm, preferably 20 to 80 mm, more preferably 30 to 60 mm.

[0021] (adhesive core-sheath composite fiber) The nonwoven fabric of the present invention contains adhesive sheath-core composite fibers in an amount of 5% by mass to 20% by mass based on the total mass of the nonwoven fabric, and the adhesive sheath-core composite fibers have adhesive joints where the fibers are bonded at their intersections. At the adhesive joints, the sheaths of the fibers are compatible with each other and can be integrated, thereby imparting good dimensional stability to the nonwoven fabric.

[0022] By including a predetermined proportion of adhesive sheath-core composite fibers, it is possible to form the bonded zone in a suitable range, thereby improving the dimensional stability of the nonwoven fabric. Furthermore, the sheaths of the adhesive sheath-core composite fibers are compatible with each other in the bonded zone, forming a pseudo-net state in which the adhesive sheath-core fibers are integrated, thereby suppressing the generation of fluff when the nonwoven fabric is rubbed. The content of the adhesive sheath-core composite fibers may be preferably 7% by mass or more and 17% by mass or less, more preferably 8% by mass or more and 15% by mass or less.

[0023] Adhesive core-sheath composite fibers are composed of a resin component that forms the core and a resin component that forms the sheath, and the sheath has adhesive properties. Various resin components can be used for the sheath as long as they are capable of forming an adhesive portion, but from the viewpoint of workability, the sheath preferably has heat-fusible properties. Preferred sheath materials include polyolefin resins such as polyethylene, polypropylene, and modified polymers, blends, and copolymers thereof, which have heat-fusible properties, as well as modified polyesters (e.g., modified polyethylene terephthalate modified with isophthalic acid), and the like. Preferred are polyethylene, modified polymers, blends, copolymers, and modified polyethylene terephthalate of polyethylene. For example, when a heat-fusible resin is used for the sheath portion, the melting point of the heat-fusible resin may be, for example, 80 to 150°C, and preferably 100 to 140°C.

[0024] On the other hand, the core is not particularly limited as long as it can be fiberized with the sheath that forms the adhesive joint and can maintain its usability as a fiber even when the sheath forms an adhesive joint, and a resin component appropriate for the sheath is selected. Preferred cores include, for example, polyolefin resins such as polypropylene and polyester resins such as polyethylene terephthalate. When a heat-fusible resin is used for the sheath, the melting point of the core resin component may be, for example, 10°C or more higher than the melting point of the sheath resin component, preferably 20°C or more higher, and more preferably 30°C or more higher.

[0025] For example, suitable core / sheath combinations include polyethylene terephthalate / polyethylene, polyethylene terephthalate / modified polyethylene terephthalate, polypropylene / polyethylene, polypropylene / modified polypropylene, etc. Among these, the combination of polypropylene / polyethylene, which is inexpensive and commonly used for nonwoven fabrics, is preferred.

[0026] From the viewpoint of forming a strong bonded joint, it is preferable that the adhesive core-sheath composite fiber is one in which the low-melting point component that forms the sheath covers at least 40% of the periphery of the core, particularly 60% or more. The composition ratio of the core to the sheath, in mass ratio, may be, for example, 90 / 10 to 10 / 90, preferably 80 / 20 to 20 / 80, and more preferably 70 / 30 to 30 / 70.

[0027] The cross-sectional shape of the adhesive sheath-core composite fiber is not particularly limited, and may be any shape, such as a circular sheath-core, an eccentric sheath-core, or a modified cross-section sheath-core. From the viewpoint of improving dimensional stability, the fineness of the adhesive sheath-core composite fiber may be, for example, 0.5 to 10.0 dtex, preferably 1.0 to 5.0 dtex, and more preferably 1.4 to 2.2 dtex. From the viewpoints of production efficiency and the mechanical properties of the nonwoven fabric, the average fiber length of the adhesive sheath-core composite fiber is preferably, for example, in the range of 10 mm to 80 mm, more preferably 30 mm to 70 mm, and even more preferably 35 mm to 60 mm. The use of such short fibers in the adhesive sheath-core composite fiber can improve the mobility and degree of entanglement of the fibers during the entanglement treatment, while also improving the mechanical properties of the nonwoven fabric, such as strength and elongation.

[0028] (Non-adhesive core-sheath composite fiber) In addition to the cellulosic fibers, the nonwoven fabric of the present invention contains non-adhesive sheath-core composite fibers having a hydrophilic and lipophilic resin as the sheath. That is, the sheath contains an ethylene-vinyl alcohol copolymer (abbreviated as EVOH) as the hydrophilic and lipophilic resin. Unlike the adhesive sheath-core composite fibers, the non-adhesive sheath-core composite fibers contain ethylene-vinyl alcohol copolymers as the sheath incompatible with each other and are present in the nonwoven fabric. The presence of such non-adhesive sheath-core composite fibers improves the elasticity of the nonwoven fabric.

[0029] The EVOH used in the sheath of the non-adhesive core-sheath composite fiber of the present invention is preferably obtained by saponifying an ethylene-vinyl ester copolymer. The EVOH component preferably has an ethylene content of 25 to 70 mol %. From the viewpoint of achieving both hydrophilicity and lipophilicity, an EVOH component having an ethylene content of 30 to 65 mol % is particularly preferred.

[0030] By using non-adhesive core-sheath composite fibers with EVOH as the sheath, the liquid retention (water retention) of the nonwoven fabric can be improved when the nonwoven fabric contains liquid components, and the nonwoven fabric can be made to retain about 30% of the liquid. Degree pressure This can improve the liquid-releasing properties when the sheet is shrunk.

[0031] In the non-adhesive core-sheath composite fiber, the core is not particularly limited as long as it is a resin component that can be formed into a fiber together with EVOH. Preferably, the core may be a hydrophobic resin component from the viewpoint of imparting rigidity to the hydrophilic EVOH.

[0032] Examples of the hydrophobic resin component include polyester-based resins such as polyethylene terephthalate, polyolefin-based resins such as polypropylene, polyamide-based resins, etc. Polypropylene and polyester-based resins are preferred from the viewpoint of higher rigidity than EVOH, and polyester-based resins are preferred from the viewpoint of higher elastic modulus and improved dimensional stability of the nonwoven fabric.

[0033] By using non-adhesive core-sheath composite fibers, it is possible to create spaces in the nonwoven fabric to hold liquid, and not only can it control the liquid-releasing properties, but also, due to the fact that it is non-adhesive, there is less friction between the nonwoven fabric and the skin, reducing the burden on the skin. Degree pressure Even when compressed, it is possible to impart a suitable compression hardness to the nonwoven fabric that is neither too hard nor too soft.

[0034] From the viewpoint of imparting both hydrophilicity and lipophilicity to the fiber surface and controlling liquid release, it is preferable that the EVOH sheath covering at least 50%, particularly 70%, of the core is used in the non-adhesive sheath-core composite fiber. The core / sheath ratio, by mass, may be, for example, 90 / 10 to 10 / 90, preferably 80 / 20 to 20 / 80, and more preferably 70 / 30 to 30 / 70.

[0035] The cross-sectional shape of the non-adhesive sheath-core composite fiber is not particularly limited, and may be any shape, such as a circular sheath-core, an eccentric sheath-core, or a modified cross-section sheath-core. From the viewpoints of processability and texture, the fineness of the non-adhesive sheath-core composite fiber may be, for example, 0.5 to 10.0 dtex, preferably 1.0 to 5.0 dtex, and more preferably 1.4 to 2.2 dtex. From the viewpoints of manufacturing workability and the mechanical properties of the nonwoven fabric, the average fiber length of the non-adhesive sheath-core composite fiber is preferably, for example, in the range of 10 mm to 80 mm, more preferably 30 mm to 70 mm, and even more preferably 35 mm to 60 mm. Non By using such short fibers in adhesive core-sheath type conjugate fibers, it is possible to improve the mechanical properties such as strength and elongation of the nonwoven fabric while increasing the mobility and degree of entanglement of the fibers during the entanglement treatment.

[0036] The content of non-adhesive sheath-core composite fibers, expressed as the mass ratio of the cellulosic fiber content (T) to the non-adhesive sheath-core composite fiber content (N), may be, for example, T / N=99 / 1 to 51 / 49, preferably 95 / 5 to 55 / 45, more preferably 95 / 5 to 65 / 35, and even more preferably 95 / 5 to 75 / 25.

[0037] Fig. 1 is a schematic perspective view illustrating a nonwoven fabric according to one embodiment of the present invention, Fig. 2 is an enlarged schematic plan view conceptually illustrating a portion of the nonwoven fabric, Fig. 3A is a partially enlarged schematic view illustrating a portion III in Fig. 2, and Fig. 3B is a partially enlarged schematic view illustrating the bonded portion in Fig. 3A.

[0038] As shown in Figure 1, nonwoven fabric 10 of the present invention contains cellulosic fibers 13, adhesive sheath-core conjugate fibers 11, and non-adhesive sheath-core conjugate fibers 14. These fibers 11, 13, and 14 may be randomly oriented in the nonwoven fabric, or may be oriented primarily in one direction (e.g., MD). In nonwoven fabric 10, adhesive sheath-core conjugate fibers 11 are bonded to each other at their intersections, thereby maintaining the shape of the nonwoven fabric.

[0039] Figure 2 is an enlarged plan view conceptually enlarging a portion of Figure 1, illustrating the state of adhesive sheath-core conjugate fiber 11 and non-adhesive sheath-core conjugate fiber 14 in a nonwoven fabric. In Figure 2, adhesive sheath-core conjugate fiber 11 and non-adhesive sheath-core conjugate fiber 14 are conceptually illustrated as linear objects. Note that cellulosic fiber 13 is also distributed as linear objects in the nonwoven fabric, but is not illustrated as such in the figure. Note that for simplicity, the figure shows it as a straight object, but either fiber may be curved.

[0040] As shown in Fig. 2, adhesive sheath core conjugate fibers 11 have adhesive parts 12 where they are bonded to each other at their intersections with other adhesive sheath core conjugate fibers 11. On the other hand, non-adhesive sheath core conjugate fibers 14 are not bonded to each other at their intersections with other non-adhesive sheath core conjugate fibers 14.

[0041] At the intersection of the adhesive sheath core conjugate fiber 11 and the non-adhesive sheath core conjugate fiber 14, the two may appear to be bonded due to the appearance of the adhesive sheath core conjugate fiber, but normally no mutually soluble bonded portion is formed at the intersection. Also, at the intersection of the adhesive sheath core conjugate fiber 11 and the cellulosic fiber 13, no mutually soluble bonded portion is formed at the intersection.

[0042] As shown in Fig. 2, the bonded regions 12 are formed by interfiber bonding at the intersections where adhesive sheath-core composite fibers 11, 11 intersect with each other, and multiple bonded regions 12 are present evenly throughout the entire web. In other words, the multiple bonded regions 12 are distributed almost uniformly throughout the entire web. In each bonded region 12, interfiber bonding is formed by fusion or welding of portions of the sheath regions 11a of the adhesive sheath-core composite fibers 11 that intersect with each other (the portions of the intersections where the fibers come into contact with each other).

[0043] Therefore, unlike simple physical entanglement, the adhesive portions 12 can form fixed points at which the nonwoven fabric is fixed. Therefore, for example, even when the nonwoven fabric is pulled, the adhesive portions 12 can serve as gripping portions, improving the shape stability of the nonwoven fabric. Furthermore, adhesive portions 12 that are close to each other can form a pseudo-net state, which makes it possible to suppress excessive stretching during use.

[0044] 3A and 3B, adhesive sheath-core conjugate fiber 11 is a conjugate fiber including sheath portion 11a and core portion 11b covered by sheath portion 11a, and adhesive portion 12 is formed at the intersection between sheath portion 11a of one adhesive sheath-core conjugate fiber 11 and sheath portion 11a of another adhesive sheath-core conjugate fiber 11. The sheath portion is not particularly limited as long as it has adhesive properties, but for example, in the case of a heat-fusible sheath-core conjugate fiber, adhesive sheath-core conjugate fiber 11 uses a low-melting point component as sheath portion 11a and a high-melting point component as core portion 11b.

[0045] The adhesive sheath-core composite fiber 11 has a cross-sectional shape when cut along a plane perpendicular to the longitudinal direction, in which the outer peripheral surface of a circular core 11b is covered with a cylindrical sheath 11a having a substantially uniform thickness in the circumferential direction. However, as described above, the cross-sectional shape of the adhesive sheath-core composite fiber is not limited to the circular core-sheath shape, and may be any shape, such as an eccentric core-sheath type or an irregular cross-section core-sheath type.

[0046] The nonwoven fabric of the present invention may contain fibers other than the above-mentioned cellulose-based fibers, adhesive sheath-core composite fibers, and non-adhesive sheath-core composite fibers, as long as the effects of the present invention are not impaired. Examples of such fibers include polyester-based fibers, polyolefin-based fibers, polyamide-based fibers, acrylic-based fibers, and polyvinyl alcohol-based fibers.

[0047] [Nonwoven fabric manufacturing method] The nonwoven fabric can be obtained by forming a web by a dry method using the various fibers described above from the viewpoint of blending the fibers and ensuring space for liquid impregnation, then entangling the fibers in the web by an entanglement treatment, and further forming adhesive parts in the adhesive core-sheath type composite fibers by an adhesive treatment.

[0048] Specifically, the cellulosic fibers, the adhesive sheath-core composite fibers, and the non-adhesive sheath-core composite fibers are blended and then opened by carding using a carding machine to produce a web. The web may be a parallel web in which the fibers are aligned in the direction of travel of the carding machine, a cross web in which parallel webs are cross-laid, a random web in which the fibers are aligned randomly, or a semi-random web in which the fibers are aligned to an intermediate degree between the two. However, a random web is preferred in view of the improved conformability in all directions when the sheet is used, and a semi-random web is preferred in view of high productivity.

[0049] The entanglement treatment is not particularly limited as long as it can entangle the fibers, but from the viewpoint of enabling dense entanglement of the fibers, it is preferable to subject the obtained web to hydroentanglement. Hydroentanglement treatment involves, for example, impinging a columnar water stream at high pressure onto a web placed on a porous support member described below, thereby densely three-dimensionally entangling and integrating the constituent fibers of the web.

[0050] A suitable method for three-dimensionally entangling a web is to place the web on a moving porous support member and treat it once or multiple times with a water stream at a water pressure of 0.5 to 15 MPa. Preferably, a nozzle plate is arranged with rows of nozzle holes in a direction perpendicular to the web's traveling direction, allowing the water stream to uniformly impinge on the web. To improve the uniformity of the web's thickness, it is preferable that the water pressure be in the range of 1.5 to 12 MPa, and that the hydroentanglement treatment be performed at least twice on each side of the web, for a total of five times or more. To ensure uniform entanglement of the web, the distance between the nozzle holes and the web is preferably 1 to 10 cm. The water stream may be sprayed from a nozzle plate having one or two rows of nozzle holes with a hole diameter of 0.05 to 0.10 mm and spaced 0.30 to 1.50 mm apart.

[0051] The porous support member on which the web is placed may be, for example, a mesh screen or a perforated plate made of metal or resin. From the viewpoint of improving the flatness of the nonwoven fabric surface, it is preferable to perform hydroentanglement on a woven structure of fine fibers (e.g., a plain weave structure) at least in the final step of the hydroentanglement treatment.

[0052] Furthermore, in order to improve the surface flatness of the web, it is preferable that the nozzle plate used in the final stage of the hydroentanglement treatment on the porous support member has injection holes with a hole diameter of 0.05 to 0.10 mm and spaced apart at intervals of 0.30 to 1.00 mm, arranged in one or two rows. <Adhesion process> In the bonding step, bonded joints are formed between the adhesive sheath-core composite fibers while maintaining the entangled structure in the web. The bonding step can be appropriately selected depending on the resin component used in the bonded joints between the adhesive sheath-core composite fibers. For example, the bonded joints may be formed in a solvent that softens only the sheath of the adhesive sheath-core composite fibers, or the bonded joints may be formed by using heat-sealed-core composite fibers and melting the sheath by heat treatment. From the viewpoint of simplicity, a bonding step using heat treatment is preferred.

[0053] The heat treatment is not particularly limited as long as it can control the temperature and other factors so as to form bonded joints in the adhesive sheath-core composite fibers while preventing the formation of bonded joints in the non-adhesive sheath-core composite fibers, and various dryers such as hot air dryers and cylinder dryers can be used. In the heat treatment step, the amount of heat can be adjusted so that the temperature of the web is higher than the melting point of the sheath of the adhesive sheath-core composite fibers contained in the web. The web with bonded joints formed therein can be used as the nonwoven fabric of the present invention.

[0054] In the case of a heat-fusion sheath-core conjugate fiber, a cooling step may be further carried out to fix the bonded portions. The cooling step may be carried out by appropriately adjusting the time from the heat treatment step until winding to release heat from the web, or by using a cooling means. In order to fix the bonded portions and improve the shape stability and fuzz prevention of the web, it is preferable to wind the web after the temperature of the web has reached the melting point temperature of the sheath portion of the heat-fusion sheath-core conjugate fiber.

[0055] [Nonwoven fabric] The nonwoven fabric of the present invention is a nonwoven fabric containing cellulosic fibers, adhesive sheath-core conjugate fibers, and non-adhesive sheath-core conjugate fibers, wherein the adhesive sheath-core conjugate fibers have adhesive portions where they are bonded at their intersections, and the content of the adhesive sheath-core conjugate fibers is 5% by mass or more and 20% by mass or less of the total mass of the nonwoven fabric, and the content of the cellulosic fibers is 45% by mass or more and less than 90% by mass, and the sheath portion of the non-adhesive sheath-core conjugate fibers contains an ethylene-vinyl alcohol copolymer.

[0056] From the viewpoint of the liquid retention of the nonwoven fabric, the apparent density of the nonwoven fabric is, for example, 0.04 to 0.20 g / cm 3 may be in the range of 0.06 to 0.15 g / cm 3The apparent density is the value obtained by dividing the basis weight of the nonwoven fabric by the thickness. If the apparent density of the nonwoven fabric is too low, the shape stability tends to decrease, and if the apparent density of the nonwoven fabric is too high, the liquid retention capacity tends to decrease. The apparent density of the nonwoven fabric constituting the sheet of the present invention is determined by the basis weight (g / m 2 ) and thickness (mm) (apparent density of nonwoven fabric (g / cm 3 ) = basis weight (g / m 2 ) / thickness (mm) / 1000). The thickness of the nonwoven fabric is measured in accordance with 6.2 of JIS L 1913 "General nonwoven fabric testing method."

[0057] The basis weight of the nonwoven fabric is, for example, 10 to 100 g / m 2 may be in the range of 20 to 100 g / m 2 within the range of 25 to 50 g / m 2 If the basis weight of the nonwoven fabric is too low, the shape stability will decrease and the nonwoven fabric will tend to curl up when used as a liquid-impregnated sheet, whereas if the basis weight of the nonwoven fabric is too high, the amount of fiber and the amount of impregnation liquid used per sheet will increase, which will tend to be disadvantageous in terms of cost.

[0058] The thickness of the nonwoven fabric is not particularly limited, and may be, for example, in the range of 0.05 to 10 mm, preferably in the range of 0.10 to 8 mm, and more preferably in the range of 0.20 to 5 mm. If the thickness is too thin, it tends to be difficult to maintain the shape of the nonwoven fabric, and if the thickness is too thick, the sheet-like fiber aggregate tends to be too thick, resulting in insufficient entanglement between the fibers.

[0059] The nonwoven fabric of one embodiment contains adhesive sheath-core composite fibers at a predetermined content range and has adhesive joints where the adhesive sheath-core composite fibers are bonded at their intersections, resulting in excellent dimensional stability. For example, the nonwoven fabric of the present invention may have an elongation percentage of, for example, 40% or less, preferably 35% or less, and more preferably 31% or less. The elongation percentage may be 0%, but in applications requiring extensibility in the nonwoven fabric, the elongation percentage may be 5% or more, more preferably 10% or more. The elongation percentage is a value measured by the method described in the Examples section below.

[0060] The nonwoven fabric of one embodiment contains cellulosic fibers and non-adhesive core-sheath composite fibers having EVOH in the sheath at a predetermined content range, and therefore has a thickness of 30%. of It is possible to control the liquid release property when compressed. After impregnating a nonwoven fabric with a mixture of distilled water and glycerin (distilled water / glycerin mass ratio = 5 / 4) at 500 mass% relative to the mass and leaving it for 24 hours, the liquid release rate for 10 seconds when compressed and deformed by 30% may be, for example, 7 to 14%, and preferably 8 to 12%. If the liquid release rate is too low, the liquid release property will be poor, and if the liquid release rate is too high, dripping due to liquid release may occur. The liquid release rate is a value measured by the method described in the examples below.

[0061] The nonwoven fabric of one embodiment contains cellulosic fibers at a predetermined content range, and the non-adhesive core-sheath composite fibers do not have any adhesive joints that are substantially bonded to each other, so that sufficient space for retaining moisture can be secured within the nonwoven fabric. Therefore, the water retention of the nonwoven fabric may be, for example, 1145% or more, preferably 1180% or more, and more preferably 1200% or more. The upper limit of the water retention is not particularly limited, but may be, for example, about 1500%. The water retention is a value measured by the method described in the Examples below.

[0062] The nonwoven fabric of one embodiment contains cellulosic fibers and non-adhesive core-sheath composite fibers having EVOH in the sheath at a predetermined content range, and therefore may have a compression hardness of, for example, 0.750 to 1.500 N / mm, preferably 0.800 to 1.400 N / mm, and more preferably 0.850 to 1.300 N / mm. The compression hardness is a value measured by the method described in the Examples below. If the compression hardness is too low, excessive liquid leakage may occur during use. For example, liquid may be released before use by pinching the sheet out of the package or folding it. On the other hand, if the compression hardness is too high, the liquid drainage rate is likely to decrease.

[0063] The nonwoven fabric of one embodiment can form a pseudo-net state to suppress the generation of fluff, and the length of fluff generated on the nonwoven fabric may be, for example, 7.0 mm or less, preferably 6.5 mm or less, and more preferably 3.0 mm or less. The fluff length is a value measured by the method described in the Examples below. Furthermore, even if the thickness of the nonwoven fabric is thin, it is possible to suppress the length of the generated fluff, and the length of the fluff generated on the nonwoven fabric may be, for example, 10 times or less, preferably 8 times or less, and more preferably 5 times or less, the thickness of one sheet of nonwoven fabric.

[0064] In one embodiment of the nonwoven fabric, it is preferable that slippage does not occur between the nonwoven fabrics when the fabric is folded for use, and therefore the static friction coefficient (A) between the nonwoven fabrics may be, for example, 0.0550 to 0.0900, preferably 0.0600 to 0.0900, and more preferably 0.0650 to 0.0880. The static friction coefficient (A) between the nonwoven fabrics is a value measured by the method described in the Examples below, and the nonwoven fabric is used in a state containing 400% by mass of distilled water.

[0065] Since the nonwoven fabric of one embodiment preferably has smoothness when applied to the skin, the static friction coefficient (C) between the nonwoven fabric and Bioskin (artificial skin) may be, for example, 0.0450 or less, and preferably 0.0430 or less. The static friction coefficient (C) between the nonwoven fabric and Bioskin (artificial skin) is a value measured by the method described in the Examples below, and during measurement, the nonwoven fabric is used in a state containing 400 mass% distilled water.

[0066] In one embodiment of the nonwoven fabric, when folded and applied to the skin, it is preferable that the nonwoven fabrics do not slide against each other but are smooth against the skin. Therefore, the difference (AC) between the static friction coefficient (A) between the nonwoven fabrics and the static friction coefficient (C) between the nonwoven fabric and bioskin (artificial skin) may be, for example, 0.0170 to 0.1000, preferably 0.0200 to 0.0900, and more preferably 0.0300 to 0.0800.

[0067] [Liquid-impregnated sheet] The present invention includes a liquid-impregnated sheet made using the nonwoven fabric. The liquid-impregnated sheet contains at least the nonwoven fabric and a liquid described below, and is suitable for use in cleaning, cosmetic, medical, household, industrial, and other applications.

[0068] The liquid used for these purposes can be appropriately selected depending on the purpose, and may be a solution, dispersion, emulsion, etc. containing a known or commonly used active ingredient. The liquid may be an aqueous liquid such as water, an aqueous solution, or an aqueous emulsion, or may be an organic solvent or an oily liquid using an organic solvent or an organic solvent as a medium, or a mixture of these.

[0069] The amount of the liquid to be used for impregnation is not particularly limited as long as the desired effect can be obtained, and can be appropriately selected depending on the purpose. The amount of the liquid to be impregnated may be, for example, 100 to 1000 parts by mass, and preferably 150 to 800 parts by mass, relative to 100 parts by mass of the nonwoven fabric.

[0070] As the active ingredient, various cosmetic ingredients, cleansing ingredients, washing ingredients, disinfecting ingredients, medicinal ingredients, refreshing ingredients, insect repellent ingredients, coating agents, paints, finishing agents (e.g., varnishes, etc.) can be used depending on the application, and these active ingredients may be used alone or in combination of two or more.

[0071] Furthermore, known or conventional active ingredients can be used as the active ingredient, and appropriate solvents (water, ethanol, glycerin, propylene glycol, dipropylene glycol, butylene glycol, etc.), auxiliary agents (emulsifiers, chelating agents, pH adjusters, neutralizing agents, thickeners, lubricants, crystallization rate retarders, etc.), additives (ultraviolet absorbers, powders, antioxidants, preservatives, fragrances, fluorescent brighteners, antistatic agents, flame retardants, deodorizers, plasticizers, colorants, etc.), etc. can be used depending on the type of active ingredient and the intended use.

[0072] Examples of beauty ingredients (ingredients for improving the body and appearance) include whitening ingredients, anti-aging (antioxidant, anti-wrinkle, anti-sagging) ingredients, anti-inflammatory (allergy-reducing, anti-allergic) ingredients, cell activation ingredients (promoting cell turnover, repairing DNA damage), moisturizing ingredients, emollient ingredients, astringent ingredients, peeling ingredients, blood circulation-promoting ingredients, antioxidant ingredients, and warming ingredients. Preferred beauty ingredients include arbutin, kojic acid, vitamin A, vitamin C, vitamin E, astaxanthin, rucinol, acetylglucosamine, ellagic acid, tranexamic acid, linoleic acid, hydroxyproline, hydroxyproline, tocopherol and derivatives thereof, water-soluble polymers, amino acids, peptides such as EGF, sugar alcohols, sugars, mucopolysaccharides, various plant extracts, placenta extract, and capsaicin.

[0073] Cleansing ingredients include nonionic surfactants, alcohols (ethanol, polyhydric alcohols, etc.), glycol ethers, oils (mineral oils, ester oils, waxes, silicone oils, natural oils, etc.) for the purpose of cleansing the skin.

[0074] The cleaning components include, in addition to the above-mentioned cleansing components, amphoteric surfactants, cationic surfactants, anionic surfactants, solvents, alkaline agents, and the like.

[0075] Disinfectant components include chlorine-based disinfectants (chlorites such as sodium chlorite, hypochlorites such as sodium hypochlorite, chlorates such as sodium chlorate, perchlorates such as sodium perchlorate, and chlorinated cyanurates such as dichloroisopropylmethylphenol sodium cyanurate), alcohols (ethanol, isopropanol, etc.), and sex Examples include surfactants, quaternary ammonium salts (benzalkonium chloride, benzethonium chloride, etc.), and chlorhexidine.

[0076] As the medicinal ingredient, various medicinal ingredients can be used depending on the application. For example, medicinal ingredients used in compresses and the like include anti-inflammatory agents, antihistamines, steroids, analgesics and anti-inflammatory agents, and local anesthetics.

[0077] Examples of the cooling component include alcohols such as ethanol, and cooling agents such as menthol, peppermint oil, camphor, thymol, spilanthol, and methyl salicylate.

[0078] Insect repellent ingredients include eucalyptus extract, menthol, peppermint oil, and diethyltoluamide.

[0079] For example, a cosmetic face mask contains a cosmetic ingredient and a solvent, and may also contain other active ingredients, auxiliaries, additives, etc., as needed. The cleansing sheet contains a cleansing ingredient, and may also contain other active ingredients (such as cosmetic ingredients), solvents, auxiliaries, additives, etc., as needed. The cleaning wiper contains a cleaning component, and may contain other active ingredients (such as coatings, finishes, paints, etc.), solvents, auxiliaries, additives, etc., as needed. The disinfecting / virus wiper contains a disinfecting component, and may contain other active ingredients (such as moisturizing components), solvents, auxiliaries, additives, etc., as needed. The itch-relieving sheet contains a medicinal ingredient, and may also contain other active ingredients (such as a cooling ingredient or a moisturizing ingredient), solvents, auxiliaries, additives, etc., as needed. The antiperspirant sheet contains a cooling component, and may contain other active ingredients (such as astringent components and moisturizing components), solvents, auxiliaries, additives, and the like, as needed. The insect repellent sheet contains an insect repellent component, and may also contain other active ingredients (such as moisturizing components), solvents, auxiliaries, additives, and the like, as needed.

[0080] In particular, the nonwoven fabric of the present invention is sufficiently impregnated with the target liquid, has excellent liquid-releasing properties during use, and has excellent shape stability, and therefore can be suitably used, for example, as an application sheet (particularly a wiping sheet). For example, when used as an application sheet, it is possible to prevent the folded nonwoven fabric from sliding against itself, so that even if the size is larger than usual, it can be easily used in the folded state. For example, in such a case, the size of one sheet can be, for example, 200 cm 2 It may be more than 250 cm 2 The size of a single sheet can be appropriately selected depending on the application, but for example, in the case of skin care applications, the upper limit of the size of a single sheet is, for example, 1000 cm 2 It may be to some extent.

[0081] Furthermore, the liquid-impregnated sheet of the present invention is useful as a skin care sheet containing the above-mentioned active ingredients and applied to the skin, taking advantage of its water retention, liquid release rate, and pleasant feel. The skin care sheet may be a sheet for rubbing, that is, a sheet for rubbing the skin, or a sheet for non-rubbing, that is, a sheet for not rubbing the skin.

[0082] The liquid-impregnated sheet of the present invention can also be used as a sheet for non-rubbing purposes, such as a cosmetic sheet impregnated with a cosmetic ingredient (for example, a cosmetic mask, a nail care sheet, a scalp care sheet, a body care sheet for the back, chest, abdomen, etc., a hygiene sheet, etc.), or a medicinal or therapeutic sheet (such as an itch-relieving sheet or a compress).

[0083] On the other hand, by using a nonwoven fabric having an appropriate compressive hardness and liquid-shedding rate (especially a nonwoven fabric that can suppress fuzzing due to friction) as the substrate, the liquid-impregnated sheet of the present invention can also be suitably used as a sheet for rubbing. Examples of sheets for rubbing include makeup removal or cleansing sheets impregnated with a wiping cleansing agent, body cleansing sheets (sweat wipes, antiperspirant sheets, hair and scalp wipes, bottom wipes, hygiene sheets, etc.), insect repellent sheets, cooling sheets, and medicated or therapeutic sheets (itch-reducing sheets, etc.). In particular, when removing eye makeup, even though the area around the eyelids is an extremely delicate skin area, a large amount of cosmetic ingredients must be removed due to heavy eye makeup. However, the liquid-impregnated sheet of the present invention is particularly useful as a makeup removal sheet because it can sufficiently shed liquid without causing any burden to the skin and is compatible with both lipophilicity and hydrophilicity due to the ethylene-vinyl alcohol copolymer. [Example]

[0084] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples and comparative examples, various physical properties were measured by the following methods.

[0085] [Basis weight and apparent density] According to 6.2 of JIS L 1913 "General nonwoven fabric testing method", the basis weight (g / m 2 ) was measured. Also, the apparent density (g / cm 3 ) was calculated by dividing the basis weight by the thickness.

[0086] [Thickness] 12 g / cm using a thickness measuring instrument for a circular horizontal plate with a diameter of 25.4 mm, based on JIS L 1913. 2 The thickness when the load was applied was measured and used as the thickness of the nonwoven fabric.

[0087] [Water retention capacity] Measurements were made in accordance with JIS L 1913 6.9.2 (water retention). A test piece was cut into a 10 cm square and the mass X (g) was measured. The test piece was then immersed in water for 15 minutes. One side of the test piece was then pinched and removed from the water, and the mass Y (g) was measured after 1 minute. The water retention capacity (g) was calculated from these values ​​using the following formula. Water retention amount (g)=YX

[0088] [Water retention rate] The water retention rate (%) was calculated by the following formula, where the mass of the test piece before immersion in water was divided by the water retention amount and expressed as a percentage. Water retention rate (%)=(YX) / X×100

[0089] [Compression hardness] The compression hardness at 30% compression deformation was measured by the following procedure. (1) Cut the measurement sample into eight 5 cm square pieces and measure the mass of all eight pieces. (2) Eight sheets of the sample were stacked on top of each other, and a mixture of distilled water (Fujifilm Wako Pharmaceutical Co., Ltd., product number 042-16973) and glycerin (Kenei Pharmaceutical Co., Ltd., Glycerin P "Kenae") in a ratio (mass ratio) of 5 parts distilled water to 4 parts glycerin was dripped in 0.3 cc portions from a height of 2 cm above the sample, until a total of 500% by mass had been dripped, allowing the entire surface of the sheet to be impregnated. (3) Place the mixture in a sealed environment where it will not evaporate, and leave it for 24 hours until the liquid has spread throughout the eight plates by capillary action. (4) After 24 hours, the samples were removed and, with the eight sheets stacked, measured at 16 g / cm using a thickness measuring instrument with a diameter of 25.4 mm on a horizontal circular plate, in accordance with JIS L 1913. 2 Measure the thickness E (mm) when a load of (5) Next, the sample is measured at the center of the sheet using a YAWASA measuring instrument Type MSES-0512-1-SL manufactured by Tech Gihansha Co., Ltd. under the conditions of an indenter diameter of 20.0 mm, a pressing speed of 1.0 mm / s, and a maximum load of 5.0 N, to determine the rebound stress. (6) From the obtained data, the sheet thickness E (mm) × 30% strain F (mm) was set as the center, and the stress (N) applied when the strain changed 0.25 mm above and below from that point was read, and the difference was divided by 0.5 mm to obtain the compression hardness (N / mm) at 30% compression deformation.

[0090] [Liquid release rate] The liquid release rate at 30% compression deformation was measured using the following procedure. (1) Cut the measurement sample into eight 5 cm square pieces and measure the mass G (g) of the eight pieces. (2) Eight sheets of the sample were stacked on top of each other, and a mixture of distilled water (Fujifilm Wako Pharmaceutical Co., Ltd., product number 042-16973) and glycerin (Kenei Pharmaceutical Co., Ltd., Glycerin P "Kenae") in a ratio (mass ratio) of 5 parts distilled water to 4 parts glycerin was added dropwise in 0.3 cc increments from a position 2 cm above the sample, resulting in a 500% mass fraction of the sample being impregnated over the entire surface of the sheet. (3) Place the mixture in a sealed environment where it will not evaporate, and leave it for 24 hours until the liquid has permeated all eight sheets by capillary action. (4) After 24 hours, the samples were removed and, with the eight sheets stacked, measured at 16 g / cm using a thickness measuring instrument with a diameter of 25.4 mm on a horizontal circular plate, in accordance with JIS L 1913. 2 Measure the thickness E (mm) when a load of (5) Place the sample on the measuring table, place absorbent cotton H (g) whose mass has been measured in advance at a position 2 cm away from the sample, and slowly slide the pressure plate to the thickness E (mm) of the sample to sandwich the sample and absorbent cotton. (6) As shown in Figure 4, the measurement stage is rotated 90 degrees to position the sample vertically. Figure 4 is a schematic side view illustrating how the liquid released from the sample is absorbed by the absorbent cotton in the liquid release rate test. After rotation, the measurement stage 24 holds the sample 20 and the absorbent cotton 22 vertically, one above the other. Because the sample 20 is positioned above the absorbent cotton 22, when the sample 20 is compressed by the movement of the pressure plate 23, the mixed liquid released from the sample 20 is absorbed by the absorbent cotton 22. (7) Specifically, the sample is compressed from thickness E to a position where it is compressed by 30% in the thickness direction. 2 3 is moved at a speed of 0.2 mm / sec to compress the sample 20 for a total of 10 seconds, and the mixed liquid released from the sample 20 is absorbed by the absorbent cotton 22. (8) The mass I (g) of the absorbent cotton 22 that has absorbed the mixed liquid is measured. From this, the liquid release rate J (%) from the sample was calculated using the following formula. Liquid discharge rate J(%)=(IH) / (G×5)×100

[0091] [Static friction coefficient between liquid-impregnated nonwoven fabrics] The friction force was measured using a precision universal testing machine ("Autograph AGS-D" manufactured by Shimadzu Corporation) in accordance with ASTM-D1894.

[0092] First, as shown in FIGS. 5 and 6, a sample 30 measuring 4.0 cm in the MD direction and 6.0 cm in the CD direction was cut from the obtained nonwoven fabric, and a friction-receiving member 35 measuring 6.0 cm in the MD direction and 12.0 cm in the CD direction was prepared. For sample 30 in FIG. 5, a 1 cm width from the edge in the CD direction was designated as gripping portion 31a, and the remaining 5 cm width was designated as ground-contact portion 31b. For friction-receiving member 35 in FIG. 6, a 1 cm width from the edge in the CD direction was designated as gripping portion 35c, and the remaining 11 cm width was designated as ground-contact portion 35d. Furthermore, assuming a cleansing sheet, both sample 30 and friction-receiving member 35 were impregnated with 400% by mass of distilled water (Fujifilm Wako Pharmaceutical Co., Ltd., product number 042-16973).

[0093] Next, as shown in Figures 7 and 8, sample 30 was placed on friction member 35, and a test was performed in which sample 30 was placed on friction member 35, and gripped at gripping portion 31a with clip 36, and sample 30 was pulled in the direction of the arrow while a predetermined load was applied from weight 38 via acrylic plate 37.

[0094] Specifically, in a precision universal testing machine equipped with a load cell 32, a friction target member 35 was placed on a table 39, and a sample 30 was placed on the friction target member 35. The sample 30 and the friction target member 35 had gripping portions 31a and 35c arranged in opposite directions, respectively, and these gripping portions 31a and 35c were held by clips 36.

[0095] Next, an acrylic plate 37 of the same size was placed on the area of ​​MD 4.0 cm × CD 5.0 ​​cm (ground contact area) of the sample 30, and the total weight of the acrylic plate 37 and the weight 38 was 3.75 g / cm 2 With the load applied, the polyamide thread 34 was pulled horizontally via the pulley 33, and the sample 30 was pulled horizontally in the CD direction at a speed of 100 mm / min, and the static friction coefficient was calculated from the test force obtained.

[0096] [Static friction coefficient between liquid-impregnated nonwoven fabric and Bioskin] The friction force was measured using a precision universal testing machine ("Autograph AGS-D" manufactured by Shimadzu Corporation) in accordance with ASTM-D1894.

[0097] First, as shown in Fig. 9, a sample 30 measuring 4.0 cm in the MD direction and 11.0 cm in the CD direction was cut out from the obtained nonwoven fabric. In sample 30 shown in Fig. 9, a 1 cm width from the edge in the CD direction was designated as a gripping portion 31a, and the remaining 10 cm width was designated as a contact portion 31b. Furthermore, assuming a cleansing sheet, this sample was impregnated with 400 mass% distilled water (manufactured by Fujifilm Wako Pharmaceutical Co., Ltd., product number 042-16973).

[0098] Next, as shown in Figures 7 and 8, sample 30 was placed on friction member 35, and gripping portion 31a of sample 30 was held with clip 36. A predetermined load was applied from weight 38 via acrylic plate 37, and a test was performed in which sample 30 was pulled in the direction of the arrow (CD direction).

[0099] In this test, (i) the friction target member 35 was a Bioskin Plate manufactured by Viewlux Co., Ltd., product number P001-001, (ii) the contact area of ​​the sample 30 was set to a range of MD 4.0 cm × CD 10.0 cm, and (iii) the total load of the acrylic plate 37 of the same size and the weight 38 placed on the contact area was set to 5 g / cm. 2 The static friction coefficient was calculated by carrying out the test in the same manner as for the static friction coefficient between nonwoven fabrics, except for the above.

[0100] [Fuzz length] The fluff length was measured using a precision universal testing machine ("Autograph AGS-D" manufactured by Shimadzu Corporation) in accordance with ASTM-D1894.

[0101] First, a sample 30 measuring 7.0 cm in the MD direction and 4.0 cm in the CD direction was cut out from the obtained nonwoven fabric, as shown in Fig. 10. In sample 30 of Fig. 10, a 1 cm width from the edge in the MD direction was designated as a gripping portion 31a, and the remaining 6 cm width was designated as a ground contact portion 31b.

[0102] Next, as shown in Figures 7 and 8, sample 30 was placed on friction member 35, and a test was performed in which sample 30 was pulled in the direction of the arrow while gripping portion 31a of sample 30 with clip 36 and applying a predetermined load from weight 38 via acrylic plate 37.

[0103] In this test, the test was carried out in the same manner as for the static friction coefficient between sheets, except that (i) Sankyo Rikagaku Co., Ltd. waterproof file #1000 was used as the friction target 35, and (ii) the contact area of ​​the sample 30 was set to a range of MD 6.0 cm × CD 4.0 cm. mmThe sample was pulled in the MD direction for 10 cm at a speed of 1 / min.

[0104] The sample was then removed from the testing machine, and the sample 30 was hung vertically with the gripping portion 31a facing up, and the lengths of the five longest fluffs that could be visually seen protruding from the MD end of the ground contact portion 31b of the sample were measured, and the average value was taken as the fluff length (mm) of the sample. Furthermore, the fluff length was divided by the thickness of the nonwoven fabric to determine the fluff length per thickness (1x) of the nonwoven fabric. The thickness of the nonwoven fabric was measured at 12 g / cm using a thickness measuring instrument with a circular horizontal plate of 25.4 mm in diameter, with reference to JIS L 1913. 2 is the thickness of the nonwoven fabric when a load of

[0105] [Growth rate] The elongation was measured using a precision universal testing machine (Shimadzu Corporation, "Autograph AGS-D Type") in accordance with JIS L 1913 (general short fiber nonwoven fabrics) 6.3.2 (wet tensile strength and elongation test). As shown in Figure 11, the gripping distance was 100 mm, and sample 40 was cut to a size of 2.5 cm in the MD × 12.0 cm in the CD. One line was drawn with an oil-based marker 15 mm from one end in the CD, and another line was drawn 90 mm apart. Sample 40 was placed in water at 20°C ± 2°C until it sank under its own weight, or was submerged in water for at least one hour. After absorbing a saturated amount of water, sample 40 was removed from the immersion liquid and quickly gripped by gripping portions 41a, 41a at both ends of sample 40, as shown in Figure 11, and a tensile stress of 2 N was instantly applied at a speed of 200 mm / min.

[0106] The sample 40 was then removed from the testing machine, and the sample 40 was hung vertically with one gripping portion 41a facing upward, and the distance K (mm) between the lines was measured. The elongation L (%) was calculated using the following formula. Elongation rate L (%) = K / 90 × 100-100

[0107] [Usability test] (sample) 15 Sheets cut into cm square size Fold it in four A mixture of distilled water (Fujifilm Wako Pharmaceutical Co., Ltd., product number 042-16973) and glycerin (Kenei Pharmaceutical Co., Ltd., Glycerin P "Kenae") in a ratio (mass ratio) of 5 parts distilled water to 4 parts glycerin was added dropwise in 0.3 cc increments from a height of 2 cm above the sample, resulting in a total of 450 mass% of the sheet being impregnated.

[0108] (Panel Testing) Nine subjects (women in their 20s, 30s, and 40s) applied the lipstick "Shiseido Maquillage Dramatic Rouge N RD633" to their lips, and then pinched one end of the sample between their index finger and middle finger, and the other end between their ring finger and little finger, so that the CD direction of the sample was perpendicular to the fingers.They then lightly pressed the sample with the insides of their middle and ring fingers and wiped it off horizontally twice without changing the surface. Each sample was evaluated in five categories: wiping ability, skin irritation, shape stability, fluffiness, and slip resistance between sheets.

[0109] [Wipeability] A sensory test was carried out using the method described above, and the removability was judged on the following three levels. 〇: Lipstick removal is satisfactory △: The lipstick removal was somewhat disappointing. ×: The lipstick did not come off well.

[0110] [Skin irritation] Sensory tests were carried out using the method described above, and skin irritation was assessed using the following three-level scale. 〇: Less irritating △: Slightly irritating ×: Too irritating

[0111] [Form stability] The sensory test was carried out using the method described above, and the results were judged on the following three levels according to the following criteria. After the test, the sheet was folded into four and unfolded, and measurements were taken in the CD direction to calculate the width that had expanded from the 15cm width before use. ○: Spread width is within 5mm △: Spread width is over 5mm and within 10mm ×: Spread width exceeds 10 mm

[0112] [Fluffiness] The sensory test was carried out using the method described above, and the results were judged on the following three levels according to the following criteria. After the test, the surface was leveled and the number of fibers protruding 3 mm or more from the surface was counted. 〇:0 bottles △: 1 or more but less than 5 ×: 5 or more

[0113] [Slip resistance between sheets] The sensory test was carried out using the method described above and was evaluated using the following three-level scale based on the following criteria: The number of times the sheet slid upward during wiping and the outermost surface of the sheet in contact with the lips did not slide was counted. 〇: 0 times △: 1 time ×: 2 or more times

[0114] The above five items were evaluated, and the number of people who gave a good rating for each item was taken as the sensory evaluation result. A: 7 or more people B: 4 or more and 6 or less people C: 3 or less people

[0115] When using a nonwoven fabric that has already been impregnated with a liquid or other component, it is preferable to first remove the impregnated component according to the following procedure before measuring and evaluating the above physical properties. Specifically, the nonwoven fabric impregnated with a liquid or other component is immersed in a cleaning solution for 2 hours to remove the component that has been previously impregnated into the nonwoven fabric. The amount of cleaning solution is 1000 ml per 100 cm of nonwoven fabric. 2The volume of the cleaning solution is 2 L per unit area. The volume is not particularly limited as long as it can remove the impregnated components, but for example, a 95 / 5 (volume ratio) of ion-exchanged water / neutral detergent may be used as the cleaning solution. For example, Kao Corporation's Cucute (trademark) is used as the neutral detergent, and the nonwoven fabric is left to stand in the liquid. The nonwoven fabric is then immersed in the same amount of ion-exchanged water for 2 hours, and after the cleaning solution has been removed, the nonwoven fabric is air-dried (conditions: 10°C, 65% RH, 24 hours) to minimize changes in the shape of the nonwoven fabric, and a measurement sample can be obtained.

[0116] Example 1 80 parts by mass of cellulose fiber (regenerated cellulose fiber, "Hope" manufactured by Omikenshi Co., Ltd., fineness 1.7 dtex, fiber length 40 mm), non-adhesive core-sheath composite fiber (core-sheath composite fiber consisting of polyethylene terephthalate and sheath of ethylene-vinyl alcohol copolymer (EVOH), "Sophista" manufactured by Kuraray Co., Ltd., fineness 1.7 dtex, fiber length 51 mm, core-sheath mass ratio (core 50%, sheath 50%) ) 10 parts by mass of adhesive core-sheath composite fiber (core-sheath composite fiber consisting of a core made of polypropylene and a sheath made of polyethylene, manufactured by Ube Exsymo Co., Ltd., fineness 1.7 dtex, fiber length 51 mm, core-sheath mass ratio (core 39%, sheath 61%) ) After uniformly blending with 10 parts by mass, the weight is 50 g / m 2A semi-random carded web (see Fig. 1) was prepared by a conventional method. This carded web was placed on a punching drum support with an opening ratio of 25% and a hole diameter of 0.3 mm and continuously transported in the longitudinal direction at a speed of 50 m / min. At the same time, a high-pressure water stream was sprayed from above to perform an entanglement treatment, producing an entangled fiber web (nonwoven fabric). This entanglement treatment was carried out using two nozzles with orifices each having a hole diameter of 0.10 mm spaced 0.6 mm apart along the width direction of the web (the distance between adjacent nozzles was 10 cm). The high-pressure water stream sprayed from the first nozzle row was at a water pressure of 3.0 MPa, and the high-pressure water stream sprayed from the second nozzle row was at a water pressure of 4.0 MPa. The carded web was then placed on a generally flat support with a finer mesh, and continuously transported while being entangled by spraying high-pressure water streams. This entanglement treatment was carried out using two nozzles with orifices of 0.10 mm diameter spaced 0.6 mm apart along the width direction of the web, both under the condition of a high-pressure water flow of 4.0 MPa. After further drying at 130°C, the web had a basis weight of 50.2 g / m 2 A spunlace nonwoven fabric of the above formula was obtained.

[0117] (Examples 2 and 3) A spunlace nonwoven fabric was obtained in the same manner as in Example 1, except that a semi-random carded web was produced in which the fiber composition ratio was changed as shown in Table 1.

[0118] (Comparative Examples 1 to 4) A spunlace nonwoven fabric was obtained in the same manner as in Example 1, except that a semi-random carded web was produced in which the fiber composition ratio was changed as shown in Table 1.

[0119] (Comparative Examples 5 and 6) A spunlace nonwoven fabric was obtained in the same manner as in Example 1, except that a semi-random carded web was produced using polyester fiber ("Tetoron" T-471, manufactured by Toray Industries, Inc., fineness 1.6 dtex, fiber length 51 mm) instead of the non-adhesive core-sheath composite fiber.

[0120] (Comparative Example 7) A spunlace nonwoven fabric was obtained in the same manner as in Example 1, except that the drying temperature was lowered to 110°C.

[0121] (Comparative Example 8) A spunlace nonwoven fabric was obtained in the same manner as in Example 1, except that the drying temperature was increased to 160°C.

[0122] [Table 1]

[0123] As shown in Table 1, in Comparative Example 1, the adhesive core-sheath composite fibers form the adhesive joints, allowing for control of elongation, but the low proportion of cellulosic fibers results in low water retention. Regarding compression hardness when soaked in liquid, the sheets are too soft when compressed and do not have adequate hardness (elasticity). Sensory evaluation revealed that the sheets slipped against each other during wiping, resulting in insufficient wiping performance.

[0124] In Comparative Example 2, the adhesive sheath-core composite fiber forms the adhesive joint, allowing for control of elongation. However, because the adhesive joint is formed with a high proportion of cellulosic fiber, the structure becomes too dense, resulting in low water retention and liquid release rates. Furthermore, because the non-adhesive sheath-core composite fiber with EVOH in the sheath is not included, the compression hardness during liquid impregnation cannot be controlled, resulting in excessive hardness upon compression. Furthermore, friction between Bioskin and the liquid-impregnated nonwoven fabric increases. Sensory evaluation revealed increased skin irritation and poor wiping performance due to the low liquid release rate.

[0125] In Comparative Example 3, the absence of adhesive core-sheath composite fibers makes it impossible to control elongation. Therefore, the sensory test also rated the shape stability low. However, in Comparative Example 3, the densification of the nonwoven fabric by the cellulosic fibers somewhat alleviates the decrease in elongation, and the deterioration in liquid release rate and the decrease in water retention rate are alleviated compared to Comparative Example 2. However, the resulting nonwoven fabric still has low water retention and liquid release rates. In the sensory test, the absence of adhesive regions resulted in poor shape stability, and the decreased liquid release properties caused increased irritation to the skin and worsened wiping properties.

[0126] In Comparative Example 4, since it does not contain adhesive core-sheath composite fibers, the elongation rate is high and shape stability cannot be controlled at all. Furthermore, with regard to the compression hardness when impregnated with liquid, it is too soft when compressed and does not have appropriate hardness (elasticity). In the sensory evaluation, it was evaluated as having particularly poor shape stability because it does not have adhesive parts.

[0127] In Comparative Examples 5 and 6, simple PET fibers were used instead of non-adhesive sheath-core composite fibers having EVOH in the sheath. Therefore, in Comparative Example 5, the compression hardness (elasticity) was low, and as a result, despite a high water retention rate, the liquid drainage was poor. Furthermore, in Comparative Example 6, the proportion of PET fibers was higher and the proportion of cellulosic fibers was lower than in Comparative Example 5, so the nonwoven fabric could not be densified, the compression hardness was extremely low, the liquid drainage rate was too high, and even fluffing occurred.

[0128] In the sensory evaluation, Comparative Example 5 was evaluated as having poor wiping properties due to a small amount of liquid discharge, while Comparative Example 6 not only had a large amount of liquid discharge, which made it prone to dripping, but also caused the sheets to slide against each other during wiping, resulting in insufficient wiping properties.Furthermore, the fluffiness was also evaluated as poor.

[0129] Comparative Example 7 contains adhesive core-sheath composite fibers, but has no adhesive joints, resulting in high elongation and complete inability to control shape stability. Furthermore, a large amount of fuzz is generated, and the compression hardness upon liquid impregnation is too soft upon compression, resulting in insufficient hardness (elasticity). In the sensory evaluation, not only was shape stability particularly poor, but fuzziness was also rated low due to the absence of adhesive joints.

[0130] In Comparative Example 8, not only the adhesive core-sheath composite fiber but also the non-adhesive core-sheath composite fiber had adhesive joints, resulting in excessive adhesive joints, which resulted in low water retention and liquid release rates. Furthermore, the compression hardness during liquid impregnation could not be controlled, resulting in excessive hardness upon compression. Furthermore, friction between Bioskin and the liquid-impregnated nonwoven fabric increased. Sensory evaluation revealed increased skin irritation and poor wiping performance due to the low liquid release rate.

[0131] On the other hand, in Examples 1 to 3, the adhesive joints are formed in a controlled state, which allows the elongation of the nonwoven fabric to be controlled and improves dimensional stability. Furthermore, while maintaining dimensional stability, the water retention and liquid release rates can also be set within suitable ranges. Furthermore, the sheets can maintain a predetermined frictional force to prevent slippage between the sheets, while reducing friction with Bioskin. Therefore, for example, even when the sheets are folded and used for wiping, good wiping performance can be achieved. Furthermore, sensory tests also rated the sheets favorably for dimensional stability, skin irritation, wiping performance, and ease of slippage and fluffiness between the sheets. [Industrial Applicability]

[0132] The nonwoven fabric of the present invention has excellent shape stability, water retention, and liquid release properties, and can therefore be suitably used as a liquid-impregnated sheet for face masks, application sheets, wiping sheets, etc. In particular, when folded for use, the nonwoven fabric is less likely to slip against itself, making it easy to handle, and also reduces friction between the nonwoven fabric and the skin, making it comfortable to use even when folded.

[0133] As described above, the preferred embodiment of the present invention has been described, but various additions, modifications, or deletions can be made without departing from the spirit of the present invention, and such additions, modifications, or deletions are also included within the scope of the present invention. [Explanation of symbols]

[0134] 10 Nonwoven fabric 11. Adhesive core-sheath composite fiber 11a Sheath part of adhesive core-sheath composite fiber 11b Core of adhesive core-sheath composite fiber 12 Adhesive part 13 Cellulose-based fibers 14 Non-adhesive core-sheath composite fiber 20, 30, 40 samples 22 cotton wool 23 Retaining plate 24 Measuring table 35 Friction-bearing member 31a, 41a Sample gripping part 31b Grounded part of sample 32 load cells 33 Pulley 34 Polyamide yarn 35c Grip part of friction object 35d Ground contact part of friction-bearing member 36 clips 37 Acrylic board 38 Weight 39 Table

Claims

1. A nonwoven fabric containing cellulosic fibers, adhesive sheath-core composite fibers, and non-adhesive sheath-core composite fibers, Relative to the total mass of the nonwoven fabric, The content of the adhesive core-sheath type composite fiber is 5% by mass or more and 20% by mass or less, The content of the cellulosic fibers is 45% by mass or more and less than 90% by mass, and The adhesive core-sheath type composite fiber has adhesive parts bonded at the intersections where the fibers intersect with each other, The non-adhesive core-sheath type composite fiber is a nonwoven fabric, the sheath of which contains an ethylene-vinyl alcohol copolymer.

2. 2. The nonwoven fabric according to claim 1, wherein the mass ratio of the content (T) of the cellulosic fiber to the content (N) of the non-adhesive core-sheath type composite fiber is T / N=99 / 1 to 51 / 49.

3. 3. The nonwoven fabric according to claim 1, which has an elongation percentage of 40% or less when it absorbs a saturated amount of water.

4. The nonwoven fabric according to any one of claims 1 to 3, wherein the nonwoven fabric has a compression hardness of 0.750 to 1.500 N / mm at 30% compression deformation when impregnated with a mixed solution of distilled water and glycerin (mass ratio of distilled water / glycerin = 5 / 4) in an amount of 500 mass% based on the mass of the nonwoven fabric and left for 24 hours.

5. The nonwoven fabric according to any one of claims 1 to 4, wherein when the nonwoven fabric is impregnated with a mixed liquid of distilled water and glycerin (distilled water / glycerin mass ratio = 5 / 4) in an amount of 500 mass% relative to the mass of the nonwoven fabric and left for 24 hours, the liquid release rate for 10 seconds when compressed and deformed by 30% is 7 to 14%.

6. The nonwoven fabric according to any one of claims 1 to 5, having a water retention rate of 1145% or more.

7. The nonwoven fabric according to any one of claims 1 to 6, wherein the difference (A-C) between the static friction coefficient (A) between the nonwoven fabric itself in a state where the nonwoven fabric contains 400% by mass of distilled water and the static friction coefficient (C) between the nonwoven fabric in a state where the nonwoven fabric contains 400% by mass of distilled water and bioskin (artificial skin) is 0.0170 to 0.1000.

8. The nonwoven fabric according to any one of claims 1 to 7, wherein the static friction coefficient (A) between the nonwoven fabrics in a state containing 400 mass% distilled water is 0.0550 to 0.0900.

9. The nonwoven fabric according to any one of claims 1 to 8, wherein the static friction coefficient (C) between the nonwoven fabric containing 400 mass% distilled water and bioskin (artificial skin) is 0.0450 or less.

10. The nonwoven fabric according to any one of claims 1 to 9, wherein the fluff length per unit thickness (1 unit) of the nonwoven fabric is 10 times or less.

11. A liquid-impregnated sheet comprising the nonwoven fabric according to any one of claims 1 to 10.

12. A wiping sheet comprising the nonwoven fabric according to any one of claims 1 to 10.

13. A method for producing the nonwoven fabric according to any one of claims 1 to 10, comprising the steps of: a step of forming a web having an entangled structure by performing an entanglement treatment on a web which contains cellulosic fibers, adhesive sheath-core composite fibers, and non-adhesive sheath-core composite fibers, the content of the adhesive sheath-core composite fibers being 5% by mass or more and 20% by mass or less, and the content of the cellulosic fibers being 45% by mass or more and less than 90% by mass, based on the total mass of the web; a step of forming a bonded portion between the adhesive core-sheath type composite fibers while not forming a bonded portion between the non-adhesive core-sheath type composite fibers in the web having the entangled structure.

14. The method for producing a nonwoven fabric according to claim 13, wherein the entanglement treatment is hydroentanglement.

15. 15. The nonwoven fabric according to claim 13 or 14, wherein in the step of forming the adhesive portion, heat treatment is performed at a temperature lower than the melting point of the sheath portion of the non-adhesive sheath core-type composite fiber and higher than the melting point of the sheath portion of the adhesive sheath core-type composite fiber.

Citation Information

Patent Citations

  • Nonwoven fabric sheet, and hydrous sheet and cosmetic each including the same

    JP2008261067A

  • Nonwoven fabric for wiper and method for producing the same

    JP2010084297A

  • Liquid-retaining sheet and face mask

    WO2013187404A1

  • Antibacterial nonwoven sheet, liquid-containing sheet, and face mask

    WO2015045982A1

  • Liquid-retaining sheet and face mask

    WO2015046301A1